Body and world - Todes, Samuel (MIT Press, 2001)
Body and World is the definitive edition of a book that should now take its place as a major contribution to contemporary existential phenomenology. Samuel Todes goes beyond Martin Heidegger and Maurice Merleau-Ponty in his description of how independent physical nature and experience are united in our bodily action. His account allows him to preserve the authority of experience while avoiding the tendency towards idealism that threatens both Heidegger and Merleau-Ponty. Todes emphasizes the complex structure of the human body; front/back asymmetry, the need to balance in a gravitational field, and so forth; and the role that structure plays in producing the spatiotemporal field of experience and in making possible objective knowledge of the objects in it. He shows that perception involves nonconceptual, but nonetheless objective forms of judgment. One can think of Body and World as fleshing out Merleau-Ponty's project while presciently relating it to the current interest in embodiment, not only in philosophy but also in psychology, linguistics, cognitive science, artificial intelligence, neuroscience, and anthropology. Todes's work opens new ways of thinking about problems such as the relation of perception to thought and the possibility of knowing an independent reality; problems that have occupied philosophers since Kant and still concern analytic and continental philosophy.